2017
DOI: 10.1007/s00266-017-0802-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Control by Intercostal Nerve Block After Augmentation Mammoplasty

Abstract: BackgroundIn breast augmentation with implant, there is severe pain due to damage from expansion of breast tissue and the pectoralis major. Therefore, the authors conducted this study to analyze the effectiveness of postoperative intercostal nerve block (ICNB) in reducing postoperative pain after breast augmentation with implant.MethodForty-four female patients were enrolled in the study. Just before awaking from general anesthesia, 34 cases were injected with 0.2% ropivacaine to both third, fourth, fifth, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Treatment of post-thoracotomy pain includes the use of intravenous (IV) opioids, which have limitations due to side effects of sedation and respiratory depression [ 7 , 8 ]. Intercostal nerve blocks using local anesthetics are effective, but limited by their short duration of action and potential neurotoxicity in high volume [ 9 , 10 ]. Epidural analgesia is commonly used for post-thoracotomy without CPB [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of post-thoracotomy pain includes the use of intravenous (IV) opioids, which have limitations due to side effects of sedation and respiratory depression [ 7 , 8 ]. Intercostal nerve blocks using local anesthetics are effective, but limited by their short duration of action and potential neurotoxicity in high volume [ 9 , 10 ]. Epidural analgesia is commonly used for post-thoracotomy without CPB [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the efficacy of intercostal nerve block in postoperative analgesia particularly in patients undergoing thoracotomy and mammoplasty showed that this technique was as effective as other methods in the early period. [26][27][28] Intercostal nerve block has been further reported to reduce the incidence of chronic pain after thoracotomy. [29] Despite being a simple technique, it has not gained popularity in clinical practice particularly in patients who will undergo multiple dermatome blocks since it requires several repeated injections that increase the risk of pneumothorax and local anaesthetic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, ICNBs have minimal risk for procedure-related complications. Complications after ICNBs include pneumothorax, systemic toxic reactions to local anesthetics, abscess formation, and neuritis [ 10 ]. Among them, pneumothorax can be the most severe complication; however, its incidence after ICNBs is rare and has been reported as 0.073–4% [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management of immediate postoperative pain includes the use of intravenous analgesics, botulinum toxin, glucocorticoids, muscle relaxers, nonsteroidal agents, indwelling pain catheters, paravertebral nerve blocks, and intercostal nerve blocks (ICNBs) [ 1 , 4 ]. Among them, ICNBs were introduced in mastectomy by McCann [ 9 ] as an adjunctive to general anesthesia, and the use of ICNBs has been reported to be a safe and effective method to manage immediate postoperative pain in patients undergoing tissue expander reconstruction [ 1 ] and augmentation mammoplasty [ 10 , 11 ]. ICNBs can be performed in breast reconstruction under the direct vision of the intercostal spaces intraoperatively by the operator without an anesthesiologist [ 1 ].…”
Section: Introductionmentioning
confidence: 99%